METODE SILABA TERHADAP KEMAMPUAN MEMBACA PERMULAAN ANAK DISLEKSIA KELAS 3 DI SD - Isnatunnikmah, Anif (Jurnal Pendidikan Khusus, 2016)
ABSTRACT   Dyslexia was an obstacle in the ability of reading, writing, and speech which gave effects toward the development of learning process so it was needed special method to overcome the problem. Therefore, Silaba method was used. The purpose of this research was to know the influence of Silaba method toward beginning reading ability of dyslexia children. The kind of research used was pre-experiment. The design used one group pre test and post test. The method used to collect the data was test method. For data analysis, the research used the analysis technique of statistic non parametric of sign test. Based on the data analysis it indicated that ZH = 2,05 > Z table = 1,96 in the significant level (two sides test) so it could be concluded that there was significant influence of Silaba method toward beginning reading ability to the third class of dyslexia children in SDN WediGedanganSidoarjo and SD TPI GedanganSidoarjo.     Keywords: Beginning reading ability, dyslexia, Silaba method.